THE ARCHITECTURE OF MULTI-COMPONENT DISTRIBUTED HYBRID EXPERT TRAINING SYSTEM - Оleh Shevchuk (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2016)
The paper reports on the design of a multi-component architecture of distributed hybrid expert training system that can be used for the study of knowledge base of both internal and external expert systems and artificial intelligence systems that are distributed on Internet servers and other computer networks. Expert training system is based on three groups of basic principles: cybernetic, reflecting experience of previous research of systems of artificial intelligence, expert training systems; pedagogical, determining the principles, on which pedagogical design and use of expert training systems are based; psychological, determining preconditious and understanding of pupils psychics, on which the processes of design and use of expert training systems in professional training of future specialists are based.It accounts for the efficient training through the distributed knowledge via the Internet, which greatly increases the didactic capabilities of the system.